Upaya Masyarakat Walmas Dalam Mengawal Proses Pemekaran Kabupaten Luwu Tengah - Muh Syafi'i Syahrir; Andi Yakub; Ariana Ariana (Palita: Journal of Social Religion Research, 2022)
This paper focuses on the process and efforts of the Walenrang and Lamasi (Walmas) people to keep blossoming the Luwu Tengah district that includes various segments of Walmas people. The community of students, local leaders, youth and regional officials participating in the blossoming effort is accelerating. As a socio-political process, these people dynamics reflected local people's wants which faced the central government regulation. This article analyses the function and dynamics of decentralization, that is, regional proliferation in Indonesia. The results of this study show that the Walenrang and Lamasi (Walmas) community movement has reached the requirements for meeting the new district but is constrained by the moratorium given by the central government